Improvement of Biodegradable Biocide’s Activity of Peroxyacetic Acid Basis Using Surfactants: Characterization and Stability - Esther Asensio; Fernando Sanagustín; Cristina Nerín; Milton Rosero-Moreano (Journal of Chemistry)
This paper deals with the study of the kinetics decomposition reaction of the peroxyacetic acid under influence of surfactant additives. The peroxyacetic acid shows a decomposition rate of 1.70 × 10−3 h−1 and its activation energy is 66 kJ mol−1. The influence of temperature on the reaction of spontaneous decomposition of peroxyacetic acid was studied at two seasonal periods. Peroxyacetic acid standard and four prototypes of biocide samples with known concentration of peroxyacetic acid and hydrogen peroxide were studied. Finally, a factorial analysis ANOVA was carried out to establish significant differences (p<0.003) between the four biocide samples over time with respect to peroxyacetic acid and hydrogen peroxide concentration. From the study carried out, it can be concluded that the biocide with surfactant substances in its composition offers the best stability and its difference versus the other biocides may guarantee a better behaviour.